Human dendritic cells contain cell surface sialyltransferase activity - Cabral, Maria Guadalupe; Piteira, A. Rita; Silva, Zélia; Ligeiro, Dário; Brossmer, Reinhard; Videira, Paula A. (Immunology letters, 2010)
Human monocyte-derived dendritic cells (mo-DCs) express highly sialylated structures, with recognized but poorly understood function in maturation, immunogenicity and endocytosis capacity. We have previously shown that mo-DCs surface sialylation is changeable upon different stimuli, which led us to hypothesise the existence of cell surface (non-intracellular) sialyltransferases, rapidly restoring or altering mo-DC surface sialylation, thus modulating specific functions. Here, we demonstrate that, in the presence of exogenous CMP-Neu5Ac, mo-DCs incorporate considerable amounts of sialic acids into cell surface, predominantly when mo-DCs were previously desialylated or matured. This is a genuine sialyltransferase activity, confirmed by specific inhibition assays, which is not influenced by secreted enzymes. Functionally, the ecto-sialyltransferase activity causes a significant down-regulation of mo-DCs endocytic capacity, without affecting the maturation state. These findings suggest that ecto-sialyltransferases participate in a dynamic control of mo-DC sialylation, with functional repercussions. This activity is possibly related with specific physiological and pathological conditions, as inflammation and infection, contributing to protection and homeostasis regulation.
Gesehen am 01.06.2023